Radiation dose reduction: comparative assessment of publication volume between interventional and diagnostic radiology - Hansmann, Jan; Henzler, Thomas (Diagnostic and interventional radiology, 2017)
PURPOSE We aimed to quantify and compare awareness regarding radiation dose reduction within the interventional radiology and diagnostic radiology communities. METHODS Abstracts accepted to the annual meetings of the Society of Interventional Radiology (SIR), the Cardiovascular and Interventional Radiological Society of Europe (CIRSE), the Radiological Society of North America (RSNA), and the European Congress of Radiology (ECR) between 2005 and 2015 were analyzed using the search terms “interventional/computed tomography” and “radiation dose/radiation dose reduction.” A PubMed query using the above-mentioned search terms for the years of 2005-2015 was performed. RESULTS Between 2005 and 2015, a total of 14 520 abstracts (mean, 660±297 abstracts) and 80 614 abstracts (mean, 3664±1025 abstracts) were presented at interventional and diagnostic radiology meetings, respectively. Significantly fewer abstracts related to radiation dose were presented at the interventional radiology meetings compared with the diagnostic radiology meetings (162 abstracts [1% of total] vs. 2706 [3% of total]; P < 0.001). On average 15±7 interventional radiology abstracts (range, 6-27) and 246±105 diagnostic radiology abstracts (range, 112-389) pertaining to radiation dose were presented at each meeting. The PubMed query revealed an average of 124±39 publications (range, 79-187) and 1205±307 publications (range, 829-1672) related to interventional and diagnostic radiology dose reduction per year, respectively (P < 0.001). CONCLUSION The observed increase in the number of abstracts regarding radiation dose reduction in the interventional radiology community over the past 10 years has not mirrored the increased volume seen within diagnostic radiology, suggesting that increased education and discussion about this topic may be warranted.